Challenges and Strategies in Implementing the Independent Curriculum to Improve Students' Critical Thinking (Case Study in Grade 4 Sciences) - Fadila, Rahma Isnaini; Hanifah, Nurdinah; Rukmana, Kusman (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The implementation of the Independent Curriculum in elementary schools in Ciamis Regency faces challenges in developing students' critical thinking skills, especially in Natural and Social Sciences (IPAS) subjects that focus on social aspects. The challenges include limited teacher understanding, less contextual learning resources, and low student involvement. This study uses a qualitative approach with a descriptive method and a Case Study research design to analyze the obstacles and strategies for implementing the Independent Curriculum. The results of the study indicate that a collaborative approach between teachers, integration of local contexts, active learning methods, and gradual use of technology can improve students' critical thinking skills. In addition, the development of a curriculum that is responsive to local needs has proven effective in encouraging students to understand and evaluate social issues in more depth. This study underlines the importance of sustainable learning innovation and local community involvement as key strategies in ensuring that the Independent Curriculum is able to produce critical, creative, and relevant students in accordance with the objectives of implementing the Independent Curriculum.